2016
DOI: 10.21746/ijbio.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination in Prunus cerasoides D. Don influenced by natural seed desiccation and varying temperature in Central Himalayan region of Uttarakhand, India.

Abstract: Prunus cerasoides D. Don the Himalayan wild cherry is one lesser known multipurpose tree species of Himalaya. The tree prefers to grow on sloping grounds between the altitudes of 1200-2400 m, on all types of soils and rocks. The tree is used as a medicinal plant in Himalayan region. The fruit is edible and the pulp is used to make a cherry brandy. The species has poor germination and seedling establishment in natural habitat. The over exploitation of seeds of the species coupled with relatively hard seed coat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Similarly in Myrica esculenta [35] found that correlation between seed moisture content and germination was negative. Tewari and Tewari [36] also reported the negative correlation between seed moisture content and germination in P. cerasoides in A. indica by [37].…”
Section: Nutritive Valuementioning
confidence: 88%
“…Similarly in Myrica esculenta [35] found that correlation between seed moisture content and germination was negative. Tewari and Tewari [36] also reported the negative correlation between seed moisture content and germination in P. cerasoides in A. indica by [37].…”
Section: Nutritive Valuementioning
confidence: 88%
“…Seed coat of Fraxinus species proved to be a more influence factor that the high ABA concentration in the embryonic axis, since the removal of the coat allowed the embryo to grow [18] . Manual removal of seed coat from Prunus cerasoides D. Don [27] , P. yedoensis Matsum [26] and mango varieties [28] , also promoted increased and accelerated the germination process.…”
Section: Pre-germinative Treatmentsmentioning
confidence: 96%